Hamster neogenin, a host-cell protein contained in a respiratory syncytial virus candidate vaccine, induces antibody responses in rabbits but not in clinical trial participants. Issue 6 (2nd June 2020) - Steff, Ann-Muriel; Cadieux-Dion, Chanel; de Lannoy, Gaël; Prato, Maria Key; Czeszak, Xavier; André, Bruno; Ingels, Dominique C; Louckx, Marc; Dewé, Walthère; Picciolato, Marta; Maleux, Koen; Fissette, Laurence; et al.
ABSTRACT: A recombinant respiratory syncytial virus (RSV) fusion glycoprotein candidate vaccine (RSV-PreF) manufactured in Chinese hamster ovary cells was developed for immunization of pregnant women, to protect newborns against RSV disease through trans-placental antibody transfer. Traces of a host-cell protein, hamster neogenin (haNEO1), were identified in purified RSV-PreF antigen material. Given the high amino-acid sequence homology between haNEO1 and human neogenin (huNEO1), there was a risk that potential vaccine-induced anti-neogenin immunity could affect huNEO1 function in mother or fetus. Anti-huNEO1 IgGs were measured by enzyme-linked immunosorbent assay in sera from rabbits and trial participants (Phase 1 and 2 trials enrolling 128 men and 500 non-pregnant women, respectively; NCT01905215/NCT02360475) collected after immunization with RSV-PreF formulations containing different antigen doses with/without aluminum-hydroxide adjuvant. In rabbits, four injections administered at 14-day intervals induced huNEO1-specific IgG responses in an antigen-dose- and adjuvant-dependent manner, which plateaued in the highest-dose groups after three injections. In humans, no vaccination-induced anti-huNEO1 IgG responses were detected upon a single immunization, as the values in vaccine and control groups fluctuated around pre-vaccination levels up to 90/360 days post-vaccination. A minority of participants had anti-huNEO1 levels ≥ assay cutoff before vaccination, which did not increase post-vaccination. Thus, despite detecting vaccine-induced huNEO1-specific responses in rabbits, we found no evidence that the candidate vaccine had induced anti-huNEO1 immunity in human adults. The antigen purification process was nevertheless optimized, and haNEO1-reduced vaccines were used in a subsequent Phase 2 trial enrolling 400 non-pregnant women (NCT02956837), in which again no vaccine-induced anti-huNEO1 responses were detected. PLAIN LANGUAGE SUMMARY: What is the context? An investigational vaccine aiming to protect newborn infants against respiratory syncytial virus (RSV) disease through immunization of pregnant women was found to contain traces of a host cell protein, i.e. hamster-derived neogenin. As hamster neogenin displays a high sequence homology with its human counterpart, there was a risk that vaccinated pregnant women could develop antibodies cross-reacting with human neogenin, which could potentially alter the function of this protein. In humans, neogenin is thought to be involved in the regulation of several developmental processes. What is new? To assess the potential of the traces of hamster neogenin to induce cross-reactive antibodies, we developed an assay to detect and quantify antibody responses specific to neogenin in rabbits and humans vaccinated with different formulations of this RSV vaccine. Rabbits developed anti-neogenin antibodies after repeated vaccination, with higher levels observed at higher vaccine doses and in the presence of aluminum hydroxide (alum) adjuvant. In contrast, no anti-neogenin antibodies were induced in male and non-pregnant female participants from three clinical trials who received a single dose of non-adjuvanted or alum-adjuvanted vaccine. These results show that the rabbit model was not predictive of the immunogenicity of this host cell protein in humans. What is the impact? In human participants, the investigational vaccine did not induce antibody responses that could cross-react with human neogenin, in contrast to the observation made in rabbits. Although the presence of this host cell protein was thus shown to unlikely represent a risk to vaccinees, the vaccine manufacturing process was modified to reduce the amount of hamster neogenin in clinical vaccine lots for subsequent trials.